ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9414789
|View full text |Cite
|
Sign up to set email alerts
|

Sound Event Detection and Separation: A Benchmark on Desed Synthetic Soundscapes

Abstract: We propose a benchmark of state-of-the-art sound event detection systems (SED). We design synthetic evaluation sets to focus on specific sound event detection challenges. We analyze the performance of the submissions to DCASE 2020 Task 4 as a function of timerelated modifications (time position of an event and length of clips) and study the impact of non-target sound events and reverberation. We show that temporal localization of sound events remains a challenge for SED systems. We also show that reverberation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…This experiment has already been proposed for DCASE 2019 and DCASE 2020 submissions [7,8]. Previous analyses showed that performance consistently drop when the onsets of the sound events are located towards the end of the clips [8]. Similar performance trends are obtained with general systems [15,19,20], while systems that have been adapted for scenario 1 [14,16,17] generally show attenuated performance drop towards the end of the clips.…”
Section: Impact Of Time Localization Of the Original Eventsupporting
confidence: 52%
See 4 more Smart Citations
“…This experiment has already been proposed for DCASE 2019 and DCASE 2020 submissions [7,8]. Previous analyses showed that performance consistently drop when the onsets of the sound events are located towards the end of the clips [8]. Similar performance trends are obtained with general systems [15,19,20], while systems that have been adapted for scenario 1 [14,16,17] generally show attenuated performance drop towards the end of the clips.…”
Section: Impact Of Time Localization Of the Original Eventsupporting
confidence: 52%
“…We evaluate the systems using the evaluation sets described in Section 2.3.3. This experiment has already been proposed for DCASE 2019 and DCASE 2020 submissions [7,8]. Previous analyses showed that performance consistently drop when the onsets of the sound events are located towards the end of the clips [8].…”
Section: Impact Of Time Localization Of the Original Eventmentioning
confidence: 96%
See 3 more Smart Citations